ANALISIS PERUBAHAN STRUKTUR BIAYA PADA PROFITABILITAS DALAM PERPINDAHAN DARI COFFEE SHOP KONVENSIONAL KE COFFEE TRUCK - Nurzan, T.M Ilham; Afrianandra, Cut; Daud, Rulfah M. (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2025)
This study aims to examine how changes in cost structure affect the profitability of entrepreneurs transitioning from conventional coffee shops to coffee trucks in Banda Aceh. This research uses a descriptive qualitative method with a case study approach. Data were collected through interviews, observations, and documentation with five coffee truck entrepreneurs selected using convenience sampling. The results show that the shift from coffee shops to coffee trucks significantly reduces fixed costs such as rent, employee salaries, and utilities, while increasing operational flexibility. A more efficient cost structure enhances profitability by minimizing expenses without compromising product quality. Coffee trucks also offer higher mobility, allowing entrepreneurs to reach customers in various strategic locations. Nevertheless, challenges such as location permits and weather conditions remain important considerations. Overall, the change in cost structure from a conventional to a mobile business model has a positive impact on coffee business profitability.